Non-Territorial Autonomy An Introduction - Andeva, Marina; Dobos, Balázs; Djordjević, Ljubica; Kuzmany, Börries; Malloy, Tove H. (Springer Nature, 2023)
This Open Access textbook is a result of the work of ENTAN - the European Non-Territorial Autonomy Network. It provides students with a comprehensive analysis of the different aspects and issues around the concept of non-territorial autonomy (NTA). The themes of each chapter have been selected to ensure a multi- and interdisciplinary overview of an emerging research field and show both in theory and in practice the possibilities of NTA in addressing cultural, ethnic, religious and language differences in contemporary societies. This is an open access book.